Cultural Heritage and Natural Disasters - Nicu, Ionut Cristi; Mihu-Pintilie, Alin; Nau, Erich (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book brings together a total of six papers in an interdisciplinary way at the border of natural disasters and cultural heritage. There is a need for studying and documenting cultural heritage in Arctic landscapes, as these are the most affected by climate change. Remote sensing represents a powerful tool in the monitoring, management and safeguarding of cultural heritage. Sites included in the UNESCO World Heritage List should receive more attention from both geoscientists and social scientists. Urbanization has a short- and long-lasting effect on the conservation of cultural heritage.